224k views
3 votes
HALP ME PLSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSS

HALP ME PLSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSS-example-1
User Hgmnz
by
5.9k points

1 Answer

1 vote

Answer:

x =
-(1)/(3), y = 2

Explanation:

3x + 3y - 7 = 12x + y

6y - 12x - 1 = -45x

(3x - 12x) + (3y - y) = 7

(-12x + 45x) + 6y = 1

-3(-9x + 2y = 7)

33x + 6y = 1

27x - 6y = -21

33x + 6y = 1

60x = -20 -> x = -20/60 = -1/3

-9x + 2y = 7 -> y =
(7+9x)/(2) =
(7+9*-(1)/(3))/(2) = 2

User Mead
by
5.0k points